Developing high-performance oxygen electrodes for intermediate solid oxide cells (SOC) prepared by Ce0.8Gd0.2O2-? backbone infiltration - Aksoy, Omer Faruk; Lemieszek, Bartlomiej; Murutoglu, Murat; Karczewski, Jakub; Jasinski, Piotr; Molin, Sebastian (Springer Heidelberg, 2024)
Gd0.2Ce0.8O (2-delta) (GDC) porous backbone infiltration with La0.6Sr0.4CoO3-delta (LSC), PrOx and LSC: PrOx as a composite oxygen electrode for intermediate solid oxide cells are conducted within the scope of this work. Samples were characterized using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and electrochemical impedance spectroscopy (EIS). A uniform distribution of the infiltrated material inside the backbone and at the electrolyte-backbone interface was achieved. EIS measurements on the prepared symmetrical samples showed electrode polarization resistance (R-p) values of 0.029 Omega.cm(2), 0.23 Omega.cm(2), and 0.44 Omega.cm(2) for LSC, LSC: PrOx, and PrOx at 600 degrees C, respectively. Long-term stability measurements at 600 degrees C for 100 h showed a slight increase in polarization resistance during the measurement period. Fuel cell measurements of commercial cells (Elcogen) with porous oxygen electrode consisting of GDC infiltrated with LSC showed an increase in power density compared to the reference cell with a value of 0.53 W.cm(- 2) obtained at 600 degrees C. It is proven that infiltration via polymeric precursor into porous scaffolds as backbone oxygen electrode layer is effective and convenient method to develop high performance and stable solid oxide cells.
Keywords: Solid oxide cells; Oxygen electrode; Infiltration; LSC; Praseodymium oxide